Access to modern energy: a review of barriers, drivers and impacts. (10th July 2017) - Bonan, Jacopo; Pareglio, Stefano; Tavoni, Massimo
Abstract: Universal access to modern energy services, in terms of access to electricity and to modern cooking facilities, has been recognized as a fundamental challenge for development. Despite strong praise for action and the deployment of large-scale electrification programs and improved cookstove (ICS) distribution campaigns, few studies have shed light on the barriers to, the enablers of and the impacts of access to energy on development outcomes, using rigorous methodologies. This paper reviews this recent strand of research, trying to fill these gaps. The authors focus on the demand-side and household perspective. Their main outcomes of interest are electricity connection and ICS adoption for the analysis of barriers, time allocation, labor market outcomes and welfare for the impact analysis. They provide evidence of significant wellbeing impacts of electrification and mixed evidence for cookstoves.